Analisis Bentuk Lagu “Madiun Kampung Pesilat Indonesia” Ciptaan Hari Subagiyo - Augusta Nurroza (Universitas Negeri Surabaya, 2021)
The purpose of this research was to describe the form of the song “Madiun Kampung Pesilat Indonesia” created by Hari Subagiyo, S.I.Kom which was played by “Rasa Madu” studio under the guidance of the Education and Culture Office of Madiun Regency. This research uses a qualitative research method because the presentation of the data is descriptive by focusing on the translation of the form of the song using theory proposed by Karl-Edmund Prier SJ, namely the Science of Musical Forms. The data analyzed is the song “Madiun Kampung Pesilat Indonesia” with a duration of 9 minutes 57 seconds which the researcher translates into the application sibelius into a score by using a western music notation writing apporoach (beam notation). The action of data analysis was carried out by means of data reduction, data presentation and drawing conclusions. The results showed that the song “Madiun Kampung Pesilat Indonesia” was played in a A Major scales and had a three-part song from with a number of bars, namely 301 bars. Part A has sentences (a, b, b’ and c) on bars 1 to137. Part B has sentences (d, e, e’, f and g) on bars 138 to 237. Part C has sentences (h and a’) on bars 238 to 301. Hari Subagiyo, S.I.Kom created this song using an ansamble music format that mixes modern and traditional music.